Fecal immunochemical tests in combination with blood tests for colorectal cancer and advanced adenoma detection: systematic review - Niedermaier, Tobias; Hoffmeister, Michael; Brenner, Hermann (United european gastroenterology journal, 2018)
Background: Colorectal cancer (CRC) is a common but largely preventable cancer. Although fecal immunochemical tests (FITs) detect the majority of CRCs, they miss some of the cancers and most advanced adenomas (AAs). The potential of blood tests in complementing FITs for the detection of CRC or AA has not yet been systematically investigated. Methods: We conducted a systematic review of performance of FIT combined with an additional blood test for CRC and AA detection versus FIT alone. PubMed and Web of Science were searched until June 9, 2017. Results: Some markers substantially increased sensitivity for CRC when combined with FIT, albeit typically at a major loss of specificity. For AA, no relevant increase in sensitivity could be achieved. Conclusion: Combining FIT and blood tests might be a promising approach to enhance sensitivity of CRC screening, but comprehensive evaluation of promising marker combinations in screening populations is needed.
Gesehen am 19.03.2018
Article was first published on October 9, 2017